-3n+6=24

Simple and best practice solution for -3n+6=24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3n+6=24 equation:


n in (-oo:+oo)

6-3*n = 24 // - 24

6-3*n-24 = 0

-3*n-18 = 0 // + 18

-3*n = 18 // : -3

n = 18/(-3)

n = -6

n = -6

See similar equations:

| 6w+6=30 | | 6-3w=-18 | | -5t-6=-56 | | 4a+2=38 | | 7t-10=18 | | 2a-2=22 | | 10-7w=10 | | 3+3b=36 | | 2n-7=-27 | | 7w+3=17 | | 6b-5=-77 | | 4d-8=24 | | 4w+6=-10 | | 6k-4=44 | | -4-6n=-4 | | 4m+7=39 | | 2t+1=-21 | | -4m+7=27 | | 5t+3=33 | | -5+2b=9 | | 1+6n=67 | | -3t-2=16 | | -7t-1=-8 | | 8+3k=-22 | | 8+5w=3 | | -6x-1=-25 | | -4-3d=14 | | (25x^3-75x^2)+(-9x+27)= | | -7+7d=-91 | | 6-7x=-78 | | 2t-6=-22 | | -6x+1=67 |

Equations solver categories